Charged‐cell periodic DFT simulations via an impurity model based on density embedding: Application to the ionization potential of liquid water. Issue 1 (9th October 2018) - Tölle, Johannes; Severo Pereira Gomes, André; Ramos, Pablo; Pavanello, Michele
Abstract: Calculations of charged systems in periodic boundary conditions (PBC) are problematic because there are spurious interactions between the charges in different periodic images that can affect the physical picture. In addition, the intuitive limit of Coulomb interactions decaying to zero as the interacting charges are placed at infinite separation no longer applies, and for example total energies become undefined. Leveraging subsystem density functional theory (also known as density embedding) we define an impurity model that embeds a finite neutral or charged subsystem within an extended (infinite) surrounding subsystem. The combination of the impurity model and a consistent choice of the Coulomb reference provides us with an algorithm for evaluating the ionization potential (IP) in extended systems. We demonstrate our approach in a pilot calculation of the IP of liquid water, based on a configuration from a prior ab initio molecular dynamics (AIMD) simulation of liquid water (Genova et al., J. Chem. Phys. 2016, 144, 234105). The calculations with the impurity model capture the broadening on the ionization energies introduced by the interactions between the water molecules. Furthermore, the calculated average IP value (10.5 eV) compare favorably to experiments (9.9‐10.06 eV) and very recent simulations based on the GW approximation (10.55 eV), while at the same time outperforming density embedding calculations carried out with a naïve handling of the electrostatic interactions (about 7 eV). Abstract : Leveraging subsystem density functional theory (also known as density embedding), an impurity model that embeds a finite neutral or charged subsystem within an extended surrounding subsystem is defined. The combination of the impurity model and a consistent choice of the Coulomb reference provides a new tool for evaluating the ionization potential in extended systems. The approach is tested using liquid water as model system.